Accuracy of CBCT as modality to identify the presence of secondary mesiobuccal root canal in the maxillary first molar - Halil, Haikal; Mahidin, Mazlifa; Farahiyah, Nik Nur; Adam, Khairul Bariah Chi (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
Introduction: Successful endodontic treatment requires the clinician to be able to locate, disinfect, and obturate all canals presence in the root canal system to remove the infection and prevent re-infection. However, some canals, such as secondary mesiobuccal (MB) root canal often missed upon examination and the treatment. The success of locating these canals is determined by the methods used, a periapical radiograph and Cone Beam Computed Tomography (CBCT). The purpose of this study was to examine the sensitivity and accuracy of the periapical radiograph (PA) and CBCT on determining the presence of the secondary MB root canal. Methods: As much as 40 intact crown and intact radicular of the maxillary first molars, without root caries, root restoration, and endodontic treated, were taken as the samples. The presence of a secondary MB root canal was evaluated by a PA radiograph, CBCT, and clinical sectioning. Samples were undergone each test and sectioned after being completed the radiographic evaluation steps. Results: CBCT radiograph was successfully identifying 62.5% secondary MB root canal presence, whilst the PA radiograph has detected only 20% of the samples. The sensitivity of CBCT and PA radiograph was compared with the gold standard method, resulting 86.2 and 27.6% respectively. The statistical analysis showed that there was no significant difference between CBCT test and the gold standard (p=0.00). Conclusion: CBCT was proven to be a reliable method to detect the presence of secondary MB root canals due to its accuracy as high as the clinical sectioning compared to the PA radiograph.